(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article examines how formulaic language affects EFL learners’ writing skills, especially when it comes to test situations. Students can improve their fluency, coherence, and cohesiveness by using formulaic language, which includes fixed terms, idioms, and collocations. Although these previously taught structures make writing easier and increase self-assurance, they can also result in formulaic, uninspired responses that lack depth and originality if they are used excessively or inappropriately. The article explores the benefits and drawbacks of formulaic expressions, emphasising the value of contextual awareness and well-rounded teaching strategies. To maximise learners’ use of formulaic language, pedagogical tactics like contextualised instruction and creative adaption tasks are suggested. The article concludes by highlighting the necessity of complex evaluation standards that promote creativity and reward efficient utilisation.